An Acoustic Meta‐Skin Insulator. Issue 37 (21st July 2020) - Tong, Lei; Xiong, Zhu; Shen, Ya‐Xi; Peng, Yu‐Gui; Huang, Xin‐Yu; Ye, Lei; Tang, Ming; Cai, Fei‐Yan; Zheng, Hai‐Rong; Xu, Jian‐Bin; Cheng, Gary J.; Zhu, Xue‐Feng
Abstract: Acoustic metamaterials with artificial microstructures are attractive to realize intriguing functions, including efficient waveguiding, which requires large impedance mismatches to realize total side reflection with negligible transmission and absorption. While large impedance mismatch can be readily realized in an air environment, acoustic waveguiding in an underwater environment remains elusive due to insufficient impedance mismatch of state‐of‐the‐art metamaterials. Here, a superhydrophobic acoustic metasurface of microstructured poly(vinylidene fluoride) membrane, referred to as a "meta‐skin" insulator, which is able to confine acoustic waves in an all‐angle and wide spectrum range due to tremendous impedance mismatch at stable air/water interfaces, viz., the Cassie–Baxter state is demonstrated. By utilizing the meta‐skin insulator with broadband and high throughput, orbital‐angular‐momentum multiplexing at a high spectral efficiency and binary coding along large‐angle bending channels for bit‐error‐free acoustic data transmission in an underwater environment are demonstrated. Very different from optical and/or electrical cable communications, acoustic waves can be simply and effectively coupled into remote meta‐skin acoustic fibers from free space, which is technologically significant for long‐haul and anti‐interference communication. This work can enlighten many fluidic applications based on efficient waveguiding, such as in vivo ultrasound medical treatment and imaging. Abstract : Underwater acoustic wave confinement in an all‐angle and wide spectrum range can be realized in a meta‐skin insulator due to the tremendous impedance mismatch originating from the stable Cassie–Baxter state. Acoustic‐wave‐based underwater orbital‐angular‐momentum multiplexing and binary coding are implemented, which is promising for long‐haul and anti‐interference communication. This work also benefits in vivo ultrasound medical treatment and imaging.